Threats to the Process of Receiving Political News from Echo Chambers and Filter Bubbles on Social Media - Januškevičiūtė, Justina (Information & Media, 2022)
The intensified selective exposure of political news on social media, personalization of the news receiving process, and emerging new information phenomena, such as filter bubbles and echo chambers, call for a rethink of the role of new digital media in a democratic society. This article analyzes the possible influence of new information phenomena on social media - information wells and filter bubbles - in receiving political news. The mechanisms and conditions of the formation of echo chambers and filter bubbles in social media are discussed in detail, and results of research conducted to date proving these phenomena are briefly presented. The article examines the possibilities of disseminating political news on social media and the restrictions on accessing comprehensive political information due to new information phenomena. The problems of political partisans' perception of the news related to these restrictions, their possible extreme actions, and their influence on democratic processes are discussed.
Keywords: social media; political news; echo chambers; filter bubbles